The factorized form of `3x^(3/2) -9x^(1/2) + 6x^(-1/2)` has to be determined

`3x^(3/2) -9x^(1/2) + 6x^(-1/2)`

=> `3*x^(1/2)*(x - 3 + 2/x)`

=> `(3/sqrt x)*(x^2 - 3x + 2)`

=> `(3/sqrt x)*(x^2 - 2x - x + 2)`

=> `(3/sqrt x)*(x(x - 2) - 1(x - 2))`

=> `(3/sqrt x)*(x - 1)(x - 2)`

**The factorized form of `3x^(3/2) -9x^(1/2) + 6x^(-1/2)` = `(3*(x - 1)(x - 2))/sqrt x` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now